Vereinheitlichung des Vertragsrechts in Europa - eine Lösung auf der Suche nach dem Problem? Die Sicht der Neuen Institutionenökonomik - Dieter Schmidtchen (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2007)
It is the purpose of the paper to shed light on the question to what extent there is a need for a unified contract law in the European Union. The paper outlines a concept of constitutional uncertainty in international trade and presents a model of international transactions in the presence of a diversity of legal orders and the territoriality of law. The model is used to identify the problems emerging in contracts and the contracting process due to factors such as the multitude of legal orders and the territoriality of law. Next, the economic arguments in favour of and against harmonisation are discussed. In weighing up the costs that full harmonisation generates against the costs of constitutional uncertainty the paper considers the arguments in favour of the diversity of law to be stronger from an efficiency point of view. The paper makes a plea for freedom of choice of contract law and a free movement of judgements in the European Union. Both conditions are necessary and sufficient for a proper functioning of the internal market – but, as a matter of fact, both conditions are already met.
Keywords: K33; F15; F02; 330; constitutional uncertainty; territoriality of law; harmonisation of law; conflict of law; international private law; transaction costs